Architectural Genetic and Epigenetic Control of Regulatory Networks: Compartmentalizing Machinery for Transcription and Chromatin Remodeling in Nuclear Microenvironments - Stein, Gary S. (2010)
The regulatory machinery that governs genetic and epigenetic control of gene expression for biological processes and cancer is organized in nuclear microenvironments. Strategic placement of transcription factors at target gene promoters in punctate microenvironments of interphase nuclei supports scaffolding of co-regulatory proteins and the convergence as well as integration of regulatory networks. The organization and localization of regulatory complexes within the nucleus can provide signatures that are linked to regulatory activity. Retention of transcription factors at gene loci in mitotic chromosomes contributes to epigenetic control of cell fate and lineage commitment, as well as to persistence of transformed and tumor phenotypes. Mechanistic understanding of the architectural assembly of regulatory machinery can serve as a basis for treating cancer with high specificity and minimal off-target effects.